Protective effects of Salubrinal against H2O2-induced muscle wasting via eIF2α/ATF4 signaling pathway - Lin, Siming; Wu, Jingying; Lian, Guili; Wu, Weibin; Chen, Weixiao; Chen, Ai; Luo, Li; Xie, Liangdi (Frontiers in Pharmacology, 2025)
BackgroundEndoplasmic reticulum stress (ERS) plays a critical role in skeletal muscle physiology and pathology, though the precise mechanisms remain unclear. Salubrinal, a selective inhibitor of eIF2α dephosphorylation, has been shown as a potential therapeutic agent for various conditions, but its effects on sarcopenia are not well understood. This study investigated the protective effects of salubrinal against H2O2-induced muscle cell injury and its impact on the eIF2α/ATF4 signaling pathway.MethodsGastrocnemius muscle samples from aged mice were used and cultured C2C12 myotubes were also used to explore the effects of Salubrinal through Western blotting, immunofluorescence, and apoptosis assays.ResultsOur results demonstrated that H2O2 treatment induced significant muscle cell damage, evidenced by reduced MHC1 expression and increased apoptosis. Salubrinal, in a concentration-dependent manner, mitigated these effects, preserving MHC1 expression and reducing apoptosis. Furthermore, salubrinal enhanced the expression of p-eIF2α and ATF4, suggesting that its protective effects are mediated through the eIF2α/ATF4 pathway.ConclusionThese findings highlight salubrinal’s potential as a therapeutic agent for muscle wasting conditions, particularly those related to oxidative stress and ERS.